Modified garnet ceramic powder, PVDF (Polyvinylidene Fluoride)-based composite solid electrolyte, solid-state battery as well as preparation method and application of modified garnet ceramic powder

By coating a thin layer of cyanoethyl cellulose (PCEC) on the garnet ceramic electrolyte, the interface structure with PVDF-based polymer is regulated, and the low ion conductivity and side reaction of PVDF-based composite solid electrolyte in the prior art is solved. Serious problems have achieved higher electrochemical stability and ion transmission rate, improving the overall performance of solid-state lithium batteries.

CN119400939APending Publication Date: 2025-02-07INST OF ELECTRICAL ENG CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411822181.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing PVDF matrix composite solid electrolyte has low ionic conductivity at room temperature and is prone to side reactions when in contact with lithium metal, resulting in a decrease in electrochemical stability and mechanical properties, affecting the high energy density and safety of the battery.

Method used

By coordinating and polymerizing cyanoethyl cellulose (CEC) with garnet ceramic electrolyte, a modified garnet ceramic powder is formed, and the interface structure between garnet and PVDF-based polymer is regulated, side reactions are suppressed, and electrochemical stability is improved. and ion transfer rate.

Benefits of technology

It significantly improves the ionic conductivity and electrochemical stability of the composite electrolyte, enhances compatibility with lithium metal, and improves the discharge specific capacity and cycling performance of solid-state lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400939A_ABST
    Figure CN119400939A_ABST
Patent Text Reader

Abstract

The invention discloses modified garnet ceramic powder, a PVDF (polyvinylidene fluoride)-based composite solid electrolyte, a solid-state battery as well as a preparation method and application of the solid-state battery. The modified garnet ceramic powder comprises ceramic powder and a modified interface layer coating the outer side of the ceramic powder, the thickness of the modified interface layer is 4-8 nm; the ceramic powder is garnet ceramic electrolyte powder; the modified interface layer is a polymer film polymerized on the surface of the ceramic powder; and the polymer film is made of polycyanoethyl cellulose. According to the modified garnet ceramic powder, cyanoethyl cellulose and a garnet ceramic electrolyte are coordinated and polymerized, so that the interface structure of garnet and a PVDF-based polymer is regulated and controlled, side reactions are inhibited, interface contact is better, electrochemical stability is achieved, ion transmission is faster, and the comprehensive performance of the composite electrolyte is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state lithium metal batteries, and in particular to a modified garnet ceramic powder, a PVDF-based composite solid electrolyte, a solid-state battery, and a preparation method and application thereof. Background Art

[0002] Traditional liquid lithium-ion batteries cannot meet the growing demand for large-scale energy storage in the future due to safety issues and limited energy density. In contrast, solid-state lithium metal batteries use solid electrolytes with superior thermal stability to replace traditional flammable organic electrolytes, thereby comprehensively solving these safety issues. In addition, the excellent mechanical properties of solid electrolytes allow the use of high-capacity lithium metal in the negative electrode, thereby significantly improving the energy density of the battery. Therefore, the research on solid electrolytes has become a focus in the field of solid-state batteries. At present, the reported solid electrolytes are mainly divided into two types: organic polymer solid electrolytes and inorganic solid electrolytes. In comparison, organic polymer solid electrolytes, due to their excellent flexibility, good interfacial compatibility and easy processing, show the most potential for large-scale application. Among the various polymer solid electrolytes reported, polymer electrolytes based on PVDF have high dielectric constants, excellent electrochemical stability and good mechanical strength. These properties make it very suitable for pairing with high-voltage, high-capacity positive electrodes and lithium metal negative electrodes to achieve high-energy density batteries, and have great potential for wide application. However, its low ionic conductivity at room temperature limits further development.

[0003] To overcome this limitation, researchers have invested a lot of effort to improve the ionic conductivity of PVDF-based polymer electrolytes. It is worth noting that the introduction of active fillers with high ionic conductivity and chemical stability, such as garnet-type ceramic electrolytes, into the PVDF matrix to form a composite polymer electrolyte has been considered an effective strategy. The active garnet-type ceramic electrolyte can not only reduce the crystallinity of the PVDF polymer matrix and promote the dissociation of lithium salts, but also enhance the mechanical strength of the electrolyte. However, the high activity of La atoms on the surface of the ceramic filler is prone to produce a Lewis base effect, which will trigger the chemical defluorination reaction of the PVDF polymer. After the defluorination reaction, the PVDF polymer shows a strong gelation tendency, resulting in poor fluidity of the slurry before the components are fully mixed, thus affecting the uniform coating of the electrolyte membrane. In addition, the unsaturated PVDF molecules have a higher highest occupied molecular orbital energy, which makes them easy to decompose at high voltage, thereby reducing the charging voltage of the electrolyte. More importantly, when in contact with lithium metal, the defluorination reaction in the unsaturated PVDF continues, resulting in further degradation of the polymer structure and serious deterioration of its mechanical properties. At the same time, the interfacial impedance between the electrode and the electrolyte increases and the ionic conductivity decreases. Eventually, the lithium dendrites penetrate the electrolyte membrane, causing the battery to short-circuit rapidly and fail. It can be seen that the violent side reactions between garnet and PVDF impair the chemical and electrochemical stability of the electrolyte, making it unsuitable for high-voltage positive electrode materials (such as high-nickel ternary materials and lithium cobalt oxide, etc.). Therefore, it is urgent to develop new strategies to design PVDF-based composite solid electrolytes with high ionic conductivity, excellent oxidation stability, and good electrode compatibility to meet the needs of high-energy-density solid-state lithium metal batteries. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a modified garnet ceramic powder, which coordinates and polymerizes CEC (cyanoethyl cellulose) and garnet ceramic electrolyte to regulate the interface structure between garnet and PVDF-based polymer, inhibit side reactions, make the interface contact better, electrochemically stable, and ion transmission faster, thereby improving the comprehensive performance of the composite electrolyte.

[0005] A further technical problem to be solved by the present invention is to provide a method for preparing modified garnet ceramic powder.

[0006] The present invention further aims to solve the technical problem of providing a PVDF (polyvinylidene fluoride) based composite solid electrolyte and a preparation method thereof.

[0007] The invention also provides a solid-state battery.

[0008] The present invention further provides application of PVDF-based composite solid electrolyte.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] A modified garnet ceramic powder, which includes ceramic powder and a modified interface layer coated on the outside of the ceramic powder; the thickness of the modified interface layer is 4-8 nm;

[0011] The ceramic powder is a garnet ceramic electrolyte powder;

[0012] The modified interface layer is a polymer film polymerized on the surface of the ceramic powder; the polymer film is polycyanoethyl cellulose (PCEC).

[0013] Among them, the garnet ceramic electrolyte powder (Li a , E b )La 3-c F c Zr 2-d M d O 12 (5 < a < 7, 0 ≤ b ≤ 0.2, 0 ≤ c ≤ 1, 0.125 ≤ d ≤ 0.6), E is Al, Ga, F is Ca, Sr, M is Nb, Ta.

[0014] The preparation method of the above-mentioned modified garnet ceramic powder, the preparation method includes the following steps:

[0015] Step 1: Dissolve the polymer monomer in a solvent to make it completely dissolved;

[0016] Step 2: Add the ceramic powder to the product of Step 1, mix evenly, and polymerize the polymer monomer on the surface of the ceramic powder;

[0017] Step 3: Dry, cool, and grind the product obtained in Step 2 to obtain the modified garnet ceramic powder.

[0018] Among them, the solvent is N, N-dimethylformamide;

[0019] And / or, the drying temperature in Step 3 is 80°C - 120°C, and the drying time is 12h - 24h;

[0020] And / or, the mass ratio of the polymer monomer to the ceramic powder is 1:2 - 1:5.

[0021] A PVDF-based composite solid electrolyte, the PVDF-based composite solid electrolyte includes a PVDF-based polymer, a lithium source, and the above-mentioned modified garnet ceramic powder.

[0022] The PVDF-based polymer includes one or more mixtures of PVDF, poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), and poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (PVDF-TrFE-CFE); the lithium source includes one or more mixtures of lithium perchlorate (LiClO4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(oxalatoborate) (LiBOB).

[0023] The preparation method of the above-mentioned PVDF-based composite solid electrolyte comprises the following steps:

[0024] Step 4: dissolving the PVDF-based polymer and the lithium source in an organic solvent to completely dissolve them to obtain a polymer solution;

[0025] Step 5: Add the modified garnet ceramic powder to the polymer solution in step 4, mix well, cast, and dry to obtain the PVDF-based composite solid electrolyte.

[0026] Wherein, the mass ratio of the PVDF-based polymer to the lithium source is 2:1 to 4:1;

[0027] and / or, the amount of the modified garnet ceramic powder added is 10-30wt% of the total mass of the PVDF-based polymer and the lithium salt;

[0028] And / or, the organic solvent includes N, N-dimethylformamide (DMF), N, N-dimethylacetamide (DMAC), N-methylpyrrolidone (NMP).

[0029] A solid-state battery comprises the above-mentioned PVDF-based composite solid-state electrolyte.

[0030] The above-mentioned PVDF-based composite solid electrolyte is used in solid-state lithium metal batteries.

[0031] The beneficial effects of the present invention are as follows:

[0032] (1) The modified garnet ceramic powder of the present invention coordinates and polymerizes CEC with garnet ceramic electrolyte to regulate the interface structure between garnet and PVDF-based polymer, inhibit side reactions, make the interface contact better, electrochemically stable, and ion transport faster, thereby improving the comprehensive performance of the composite electrolyte.

[0033] (2) The composite solid electrolyte provided by the present invention has good stability, and the obtained solid-state lithium battery has a high discharge specific capacity and good cycle performance.

[0034] (3) The preparation method of the composite solid electrolyte provided by the present invention has a simple process, mild reaction conditions, low equipment requirements, meets the requirements of green chemistry, and is conducive to market promotion.

[0035] (4) Compared with the unmodified composite solid electrolyte, the modified composite solid electrolyte has better film-forming property, high ion conductivity, wider voltage window, and better compatibility with lithium metal, thereby improving the electrochemical performance of the all-solid-state battery. The results of the examples show that the composite solid electrolyte provided by the present invention has good stability, and the obtained solid-state lithium battery has a high discharge specific capacity and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 HRTEM images of pure LLZTO ceramic powder and PCEC-coated LLZTO ceramic powder in Example 1 of the present invention.

[0037] Figure 2 This is the AC impedance spectrum of the composite solid electrolyte obtained by mixing PVDF-HFP and LiTFSI at different temperatures.

[0038] Figure 3 This is the voltage window LSV test of the composite solid electrolyte prepared by using pure LLZTO and LLZTO coated with PCEC in Example 1 of the present invention.

[0039] Figure 4 This is a stability test of the composite solid electrolyte prepared by pure LLZTO and PCEC-coated LLZTO in Example 1 of the present invention on lithium metal.

[0040] Figure 5 This is a comparative test of the electrochemical performance of all-solid-state batteries assembled using a composite solid electrolyte prepared using pure LLZTO and LLZTO coated with PCEC in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0042] A modified garnet ceramic powder comprises a ceramic powder and a modified interface layer coated on the outside of the ceramic powder; the thickness of the modified interface layer is 2-6 nm; the ceramic powder is a garnet ceramic electrolyte powder; and the modified interface layer is a polymer film polymerized on the surface of the ceramic powder.

[0043] The present invention coordinates and polymerizes CEC with garnet ceramic electrolyte to regulate the interfacial structure between garnet and PVDF-based polymer, inhibit side reactions, make the interface contact better, electrochemically stable, ion transport faster, and improve the comprehensive performance of the composite electrolyte. The present invention coordinates garnet with cyanoethyl cellulose (CEC) through La-N bonds to produce a Lewis base effect, thereby initiating the polymerization of CEC on the surface of garnet to form a polycyanoethyl cellulose (PCEC) thin layer, and then successfully modifying the garnet ceramic particles. Specifically, garnet is coordinated with cyanoethyl cellulose (CEC) through La-N bonds to produce a Lewis base effect, thereby initiating the polymerization of CEC on the surface of garnet to form a polycyanoethyl cellulose (PCEC) thin layer, and then successfully modifying the garnet ceramic particles.

[0044] The role of PCEC in the present invention is to act as a modification layer, on the one hand, preventing side reactions from occurring when garnet contacts PVDF, and on the other hand, adsorbing and conducting lithium ions.

[0045] Preferably, the garnet ceramic electrolyte powder (Li a , E b )La 3-c F c Zr 2-d M d O 12 (5 < a < 7, 0 ≤ b ≤ 0.2, 0 ≤ c ≤ 1, 0.125 ≤ d ≤ 0.6), E is Al, Ga, F is Ca, Sr, M is Nb, Ta;

[0046] Preferably, the polymer film is polycyanoethyl cellulose.

[0047] The preparation method of the above-mentioned modified garnet ceramic powder includes the following steps:

[0048] Step 1: Dissolve the polymer monomer in a solvent to make it completely dissolved; it can be completely dissolved by vigorous stirring, and the stirring speed is 400 - 800 rpm; it can also be accelerated by heating, and the heating temperature is 50 - 80°C; preferably, the mass-volume concentration of the polymer monomer and the solvent is 0.2 - 0.4 g / mL.

[0049] Step 2: Add ceramic powder to the product of Step 1 and mix evenly to polymerize the polymer monomer on the surface of the ceramic powder; the mass ratio of the polymer monomer to the ceramic powder is 1:5 - 1:9; in order to mix evenly, vigorous stirring is also used in this step, the stirring speed is 400 - 800 rpm, and the stirring time is 3 - 6 h.

[0050] Step 3: Dry, cool and grind the product obtained in step 2 to obtain modified garnet ceramic powder. Drying is preferably carried out in a vacuum, the drying temperature is 80-120°C, and the drying time is 12-24 hours.

[0051] Furthermore, the solvent is N, N-dimethylformamide.

[0052] A PVDF-based composite solid electrolyte, the PVDF-based composite solid electrolyte comprising a PVDF-based polymer, a lithium source and the above-mentioned modified garnet ceramic powder. In the PVDF-based composite solid electrolyte, lithium salt and modified ceramic powder are uniformly dispersed in the PVDF polymer matrix. PVDF is a polymer framework, which is used to ensure close contact between the electrolyte and the electrode, maintain electrochemical stability, and increase the voltage window. The modified ceramic powder is used to increase the mechanical properties of the electrolyte and has the ability to resist lithium dendrites. Secondly, it reduces the crystallinity of the PVDF polymer, increases the degree of dissociation of the lithium salt, and promotes the rapid migration and exchange of lithium ions at the interface.

[0053] The PVDF-based polymer includes one or more mixtures of PVDF, poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), and poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (PVDF-TrFE-CFE); the lithium source includes one or more mixtures of lithium perchlorate (LiClO4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(oxalatoborate) (LiBOB).

[0054] The preparation method of the above-mentioned PVDF-based composite solid electrolyte comprises the following steps:

[0055] Step 4: dissolving the PVDF-based polymer and the lithium source in an organic solvent to completely dissolve them to obtain a polymer solution; wherein the mass ratio of the PVDF-based polymer to the lithium source is 2:1~4:1, and the organic solvent includes N, N-dimethylformamide (DMF), N, N-dimethylacetamide (DMAC), and N-methylpyrrolidone (NMP); the mass-volume ratio of the solute to the solvent is 0.1~0.15 g / mL, and stirring can also be used in this step to completely dissolve it, and the stirring speed is 400~600 rpm; the stirring time is 2~6h.

[0056] Step 5: Add the modified garnet ceramic powder to the polymer solution in step 4, mix well, and cast on a smooth glass plate by tape casting, followed by drying. After drying, the PVDF-based composite solid electrolyte film can be obtained, and the thickness of the formed film is preferably 30-60 µm. In this step, stirring is used to make the mixture evenly mixed, and the stirring speed is 500-800 rpm; the stirring time is 6-12 hours.

[0057] Preferably, vacuum drying is also used in this step, and the drying temperature is 80-120°C; the vacuum drying time is 12-24 hours; non-vacuum drying can also be used, and the drying time needs to be appropriately extended to ensure that the solvent is completely evaporated.

[0058] Preferably, the added amount of the modified garnet ceramic powder is 10-30wt% of the total mass of the PVDF-based polymer and the lithium salt.

[0059] The present invention also provides a solid-state battery, which comprises the above-mentioned PVDF-based composite solid-state electrolyte.

[0060] Example 1

[0061] This example prepares modified garnet ceramic powder.

[0062] The preparation method of the modified garnet ceramic powder of this embodiment is as follows:

[0063] Step 1: Weigh 1 g of cyanoethyl cellulose (CEC) powder and disperse it in 5 mL of N, N-dimethylformamide (DMF), heat it at 60°C, and stir it vigorously at 500 rpm until it is completely dissolved;

[0064] Step 2: Add 5 g Li to the product of step 1 6.4 LqCy 1.4 Ta 0.6 O 12 (LLZTO) ceramic powder, continue to stir vigorously at 500 rpm to allow cyanoethyl cellulose to slowly polymerize on the surface of LLZTO, stir for 4 hours until the white turbid liquid turns into a reddish brown colloid and mixes evenly, so that the polymer monomer polymerizes on the surface of the ceramic powder;

[0065] Step 3: Dry the product (colloid) obtained in step 2 in a vacuum drying oven at 100° C. for 24 hours, cool to room temperature, and grind to obtain modified garnet ceramic powder.

[0066] Figure 1 Figure (a) is the HRTEM image of pure (unmodified) LLZTO ceramic powder. Except for obvious lattice fringes, there is almost no coating layer on the crystal surface. Figure 1 Figure b is the HRTEM image of LLZTO ceramic powder after PCEC coating. In addition to the lattice fringes, it can be clearly seen that there is an amorphous PCEC coating layer on the crystal surface with a thickness of about 5 nm.

[0067] Example 2

[0068] This example prepares modified garnet ceramic powder.

[0069] The preparation method of the modified garnet ceramic powder of this embodiment is as follows:

[0070] Step 1: Weigh 1 g of CEC powder and disperse it in 3 mL of DMF, heat it at 50 °C and stir it vigorously at 500 rpm until it is completely dissolved;

[0071] Step 2: Add 6.2 g Li7La3Zr2O to the product of step 1 12 (LLZO) electrolyte powder, continue to stir vigorously at 500 rpm to allow CEC to slowly polymerize on the LLZTO surface, stir for 5 h, and the white turbid liquid turns into a reddish brown jelly;

[0072] Step 3: The reddish brown colloid obtained in step 2) was dried in a vacuum oven at 100°C for 16 h, cooled to room temperature, and ground to obtain PCEC-coated LLZO powder.

[0073] Example 3

[0074] The preparation method of the modified garnet ceramic powder of this embodiment is as follows:

[0075] Step 1: Weigh 1 g of CEC powder and disperse it in 2.5 mL of DMF. Heat it at 70 °C and stir it vigorously at 700 rpm until it is completely dissolved.

[0076] Step 2: Add 7.1 g Li to step 1) 6.1 Al 0.1 Ln3Z 1.4 Ta 0.6 O 12 (LALZTO) electrolyte powder, continue to stir vigorously at 700 rpm to allow CEC to slowly polymerize on the LALZTO surface, stir for 3 h, and the white turbid liquid turns into a reddish brown jelly;

[0077] Step 3: The reddish brown colloid obtained in step 2 was dried in a vacuum oven at 120° C. for 12 h, cooled to room temperature, and ground to obtain PCEC-coated LALZTO powder.

[0078] Example 4

[0079] The preparation method of the modified garnet ceramic powder of this embodiment is as follows:

[0080] Step 1: Weigh 1 g of CEC powder and disperse it in 4 mL of DMF. Heat it at 80 °C and stir it vigorously at 500 rpm until it is completely dissolved.

[0081] Step 2: Add 9 g Li to step 1 6.75 Ln3Z1.75 Nb 0.25 O 12 (LLZNO) electrolyte powder, continue to stir vigorously at 500 rpm to allow CEC to slowly polymerize on the surface of LLZNO, stir for 6 h, and the white turbid liquid turns into a reddish brown jelly;

[0082] Step 3: The reddish-brown colloid obtained in step 2 was dried in a vacuum oven at 80° C. for 24 h, cooled to room temperature, and ground to obtain PCEC-coated LLZNO powder.

[0083] Example 5

[0084] In this example, a PVDF-based composite solid electrolyte is prepared using the modified garnet ceramic powder prepared in Example 1.

[0085] Step 4: Weigh 0.3 g of PVDF-HFP polymer and 0.1 g of LiTFSI salt and dissolve them in 4 mL of DMF. Stir vigorously at 600 rpm for 4 h until completely dissolved and uniform.

[0086] Step 5: Add 0.06 g of the modified garnet ceramic powder obtained in Example 1 to the polymer solution in Step 4, continue stirring at 600 rpm for 10 h, build a film, control the film thickness to 50 µm, and then dry it in a vacuum dryer at 100 °C for 24 h to obtain a composite solid electrolyte.

[0087] Figure 2 a is the AC impedance spectrum of the composite solid electrolyte obtained by mixing pure LLZTO (unmodified) with PVDF-HFP and LiTFSI at different temperatures. The resistance at room temperature is 18Ω. It can be clearly seen that the electrolyte color is reddish brown due to the HF removal reaction of PVDF-HFP. After calculation, its room temperature ionic conductivity is 2.0×10 -4 S / cm 2 (The calculation formula for ionic conductivity is , where L is the thickness, R is the impedance, S is the surface area, and σ is the ionic conductivity). Figure 2 b is the AC impedance spectra of the composite electrolyte prepared in Example 5 at different temperatures. The calculated room temperature ionic conductivity is as high as 5.5×10 -4 S / cm 2 The PVDF-HFP in Example 5 does not undergo HF removal reaction, and the electrolyte is consistent with the color of the ceramic powder, which is light yellow. In addition, PCEC can make the ceramic-polymer interface contact better, the oxidation resistance is more stable, and the ion transmission is faster.

[0088] Figure 3The voltage window LSV test of two composite solid electrolytes (using unmodified garnet ceramic powder and modified garnet ceramic powder) showed that the voltage upper limit of the electrolyte CPE-1 prepared by pure LLZTO was only 4.2 V. This was because PVDF-HFP after the HF removal reaction was easily decomposed under high pressure. The electrolyte CPE-2 prepared by PCEC coated LLZTO had an upper voltage limit of 4.8 V because PVDF-HFP maintained the structural integrity and had excellent antioxidant properties, which could match almost all high-voltage positive electrode materials.

[0089] Figure 4 The stability of the two composite solid electrolytes (using unmodified garnet ceramic powder and modified garnet ceramic powder) to lithium metal was tested at 0.1 mA cm -2 Under the current density, the electrolyte CPE-1 prepared by pure LLZTO has a large overpotential of 0.3 V, and it fails after short circuit after 520 hours of cycling. This is due to the lower ionic conductivity. The electrolyte CPE-2 prepared by PCEC coated LLZTO has a higher ionic conductivity, an overpotential of only 0.1 V, and can be stably cycled for more than 1500 hours, showing excellent lithium metal compatibility.

[0090] Example 6

[0091] In this example, a PVDF-based composite solid electrolyte is prepared using the modified garnet ceramic powder prepared in Example 2.

[0092] Step 4: Weigh 0.4 g PVDF polymer and 0.15 g LiClO4 salt and dissolve them in 5 mL DMAC. Stir vigorously at 500 rpm for 6 h until completely dissolved and uniform.

[0093] Step 5: Add 0.1 g of the modified garnet ceramic powder obtained in Example 2 to the polymer solution in Step 4, continue stirring at 600 rpm for 10 h, build a film, control the film thickness to 40 µm, and then dry it in a vacuum dryer at 120°C for 18 h to obtain a composite solid electrolyte.

[0094] Example 7

[0095] In this example, a PVDF-based composite solid electrolyte is prepared using the modified garnet ceramic powder prepared in Example 3.

[0096] Step 4: Weigh 0.5 g of PVDF-TrFE-CFE polymer and 0.2 g of LiBOB salt and dissolve them in 5 mL of NMP. Stir vigorously at 600 rpm for 4 h until they are completely dissolved and uniform.

[0097] Step 5: Add 0.07 g of the modified garnet ceramic powder obtained in Example 3 to the polymer solution in Step 4, continue stirring at 600 rpm for 10 h, build a film, control the film thickness to 40 µm, and then dry it in a vacuum dryer at 120°C for 18 h to obtain a composite solid electrolyte.

[0098] Example 8

[0099] In this example, a PVDF-based composite solid electrolyte is prepared using the modified garnet ceramic powder prepared in Example 4.

[0100] Step 4: Weigh 0.3 g PVDF polymer and 0.15 g LiTFSI salt and dissolve them in 3.5 mL NMP. Stir vigorously at 600 rpm for 2 h until completely dissolved and uniform.

[0101] Step 5: Add 0.12 g of the modified garnet ceramic powder obtained in Example 4 to the polymer solution in Step 4, continue stirring at 600 rpm for 8 h, build a film, control the thickness to be 60 µm, and then dry it in a vacuum dryer at 120 ° C for 15 h to obtain a uniform composite solid electrolyte.

[0102] Example 9

[0103] In this example, a PVDF-based composite solid electrolyte is prepared using the modified garnet ceramic powder prepared in Example 4.

[0104] Step 4: Weigh 0.3 g PVDF polymer and 0.1 g LiTFSI salt and dissolve them in 3.5 mL NMP. Stir vigorously at 600 rpm for 2 h until completely dissolved and uniform.

[0105] Step 5: Add 0.12 g of the modified garnet ceramic powder obtained in Example 1 to the polymer solution in Step 4, continue stirring at 600 rpm for 8 h, build a film, control the thickness to be 60 µm, and then dry it in a vacuum dryer at 120°C for 15 h to obtain a uniform composite solid electrolyte.

[0106] Example 10

[0107] In this embodiment, a solid-state battery is prepared by using the composite solid electrolyte prepared in Examples 5 to 8 and the composite electrolyte prepared from pure garnet as the electrolyte, and the high-nickel ternary material LiNi 0.9 Co 0.05 Mn 0.05O2 (NCM9055) is the positive electrode active material, which is dissolved in NMP with Super P, PVDF and LiTFSI (the mass ratio of NCM9055, Super-P, PVDF and LiTFSI is 94:2:3:1) to form a uniform slurry, which is coated on the surface of aluminum foil and cut into discs as the positive electrode after drying. Lithium metal is used as the negative electrode, and the solid-state battery is assembled in a glove box.

[0108] The constant current charge and discharge test was carried out using the Xinwei battery test system with a voltage range of 2.8~4.3 V.

[0109] Figure 5 The electrochemical performance comparison diagram of the all-solid-state battery assembled with the two obtained composite solid electrolytes (using unmodified ceramic powder and modified garnet ceramic powder of Example 1, respectively) is shown in FIG. Figure 5 It can be seen that the battery assembled with the PCEC-modified electrolyte CPE-2 exhibits a higher discharge capacity and excellent cycle performance: the discharge specific capacity can reach 217 mAh / g at a current density of 0.1C, and the capacity retention rate reaches 85% after 100 cycles. The excellent electrochemical performance is due to its higher ionic conductivity and more stable interface contact.

[0110] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0111] The parts not elaborated in detail in the description of the present invention belong to the known technology in the art. The above embodiments are provided only for the purpose of describing the present invention, and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. Various equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be included in the scope of the present invention.

Claims

1. A modified garnet ceramic powder, characterized in that: The invention comprises a ceramic powder and a modified interface layer coated on the outside of the ceramic powder; the thickness of the modified interface layer is 4-8 nm; The ceramic powder is garnet ceramic electrolyte powder; The modified interface layer is a polymer film polymerized on the surface of the ceramic powder; the polymer film is polycyanoethyl cellulose.

2. The modified garnet ceramic powder according to claim 1, characterized in that: The garnet ceramic electrolyte powder is (Li a , E b )La 3-c F c Zr 2-d M d O 12 , where 5 < a < 7, 0 ≤ b ≤ 0.2, 0 ≤ c ≤ 1, 0.125 ≤ d ≤ 0.6, E is Al or Ga, F is Ca or Sr, and M is Nb or Ta.

3. The method for preparing the modified garnet ceramic powder according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Step 1: dissolving the polymer monomer in a solvent to make it completely dissolved; Step 2: Add ceramic powder to the product of step 1, mix evenly, and polymerize the polymer monomer on the surface of the ceramic powder; Step 3: Dry, cool and grind the product obtained in step 2 to obtain modified garnet ceramic powder.

4. The preparation method according to claim 3, characterized in that: Wherein the solvent is N, N-dimethylformamide; And / or, in step 3, the drying temperature is 80°C to 120°C, and the drying time is 12h to 24h; And / or, the mass ratio of the polymer monomer to the ceramic powder is 1:2 to 1:

5.

5. A PVDF-based composite solid electrolyte, characterized in that: The PVDF-based composite solid electrolyte comprises a PVDF-based polymer, a lithium source and the modified garnet ceramic powder according to claim 1 or 2.

6. The PVDF-based composite solid electrolyte according to claim 5, characterized in that: The PVDF-based polymer includes one or more mixtures of PVDF, poly(vinylidene fluoride-hexafluoropropylene), and poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene); the lithium source includes one or more mixtures of lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(oxalatoborate).

7. The method for preparing the PVDF-based composite solid electrolyte according to claim 5 or 6, characterized in that: The following steps are also included: Step 4: dissolving the PVDF-based polymer and the lithium source in an organic solvent to completely dissolve them to obtain a polymer solution; Step 5: Add the modified garnet ceramic powder to the polymer solution in step 4, mix well, cast, and dry to obtain the PVDF-based composite solid electrolyte.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the PVDF-based polymer to the lithium source is 2:1 to 4:1; and / or, the amount of the modified garnet ceramic powder added is 10-30wt% of the total mass of the PVDF-based polymer and the lithium salt; And / or, the organic solvent includes N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone.

9. A solid-state battery, characterized in that: It includes the PVDF-based composite solid electrolyte as described in claim 5 or 6.

10. Use of the PVDF-based composite solid electrolyte according to claim 5 or 6 in a solid-state lithium metal battery.

Citation Information

Cited By

  • Wide-temperature-range PVDF-based polymer solid-state electrolyte membrane, preparation method and solid-state battery

    CN121123382A